(untitled) (World of finance, 2019)
Introduction. Today the problem of establishing an effective taxation technology of domestic insurers’ financial results has not been finally solved. That technology would ensure achieving fiscal objectives of budget revenues improvement and the implementation of the regulatory capacity of the tax regime to enhance the development of the insurance market in Ukraine on the principles of transparency and legitimacy of the business. Purpose. The purpose of the article is critical analysis of recent transformations in the method of taxation of the financial performance of insurance companies in Ukraine, assessment of their impact on the dynamics of national insurance organizations budget revenues in recent years, a clear identification of legal conflicts and problematic aspects of the insurers’ profit and income tax collecting procedures with a view to their elimination. Results. The article looks into the major differences in innovation and methodological approaches to taxation of the financial performance of domestic insurers before and after January 1, 2015. The work characterizes the dynamics of absolute and relative indicators of income tax on profits from insurance companies to the consolidated budget of Ukraine in 2012-2016 (compared to banks) from a position of impact of changes in tax regime for insurers. The research also revealed a number of legal contradictions and problematic issues in the current procedure for determining taxable profits of insurance organizations in the consideration of tax differences, calculating the income tax of taxable item in the neglecting of the revenues and transmission of insurance payments (contributions, premiums) for reinsurance operations and so on. Conclusion. A number of recommendations to improve the technology of direct taxation of insurance companies’ corporate income tax and indirect taxes on insurance premiums, namely: clear distinction of mentioned fiscal duties; revision of the legal framework regarding the collection of insurers’ income tax (detailed definition of the list of costs for the calculation of financial results of the insurer before tax, establishing a list and approval of scientifically based methods of calculating insurance reserves for the calculation of taxable income, specification of legal provisions regarding taxation of insurance companies that specialize in life insurance, and longterm pension insurance); the introduction of preferential tax treatment of small profit insurance organizations through the establishment of progressive tax rates; gradual reduction of the effective tax rate for insurance companies.